Gender Inequality in Nigeria Football: A Critical Analysis of Media Coverage and Sponsorship - Ikechukwu, Okeke Noble; Funmi Falobi; Joseph Ifeoluwa Joy; Samuel Onyebuenyi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2026)
Football remains one of the most influential sports globally, attracting massive audiences and significant media attention, with over 250 million players and 1.3 billion followers worldwide. In Nigeria, the sport holds deep cultural significance, serving as a unifying force that fosters national identity, social cohesion, and economic opportunities through media broadcasting, sponsorship, and youth engagement. Despite this prominence, the development and recognition of football in Nigeria are marked by persistent gender inequalities. While men’s football enjoys extensive media coverage, structured leagues, and substantial sponsorship investment, women’s football—despite notable achievements such as the dominance of the Super Falcons in African competitions—remains underrepresented and underfunded. This study critically examines disparities in media coverage, sponsorship, and public perception between men’s and women’s football in Nigeria. Drawing on secondary data and supported by Agenda-Setting Theory, the paper argues that the disproportionate visibility given to men’s football by Nigerian media shapes public attitudes, reinforces cultural stereotypes, and influences the allocation of financial resources in favor of male teams. The findings reveal that limited media attention, biased reporting patterns, and unequal sponsorship structures collectively marginalize women’s football, restricting its growth and diminishing its competitive potential. The study concludes that without deliberate efforts to ensure balanced media representation and equitable investment, gender inequality in Nigerian football will persist, undermining both the development of the sport and the broader goal of gender inclusion.